INHIBITORY POWER OF MAS BANANA PEEL EXTRACT (MUSA ACUMINATA LADY FINGER) ON THE GROWTH OF STAPHYLOCOCCUS AUREUS IN VITRO - Dwis Syahrul; Ni Putu Widani Astuti; Dwis Syahriel; Desak Putu Diah Pradnyani; M. Dian Firdausy (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Various sources of infectious disease can be found in the oral cavity. Prevention efforts include brushing your teeth properly and regularly. Besides that, gargling with mouthwash is one of the best additional prevention methods. In the literature it is known that mas banana peels contain antibacterial ingredients. The aim of this research was to determine whether banana peel extract (Musa acuminata lady finger) was able to inhibit the growth of Staphylococcus aureus bacteria. Material and Methods: Extracts of 25%, 50%, 75% concentration of dried mas banana peel were made, sterile distilled water as a negative control and 0.2% Chlorhexidine as a positive control. Staphylococcus aureus ATCC 25923 as many as 3 bacterial colonies, spread evenly on sterile Nutrient Agar (NA) media. The paper discs were dipped for ± 30 seconds into 25%, 50%, 75% gold banana peel extract, 0.2% Chlorhexidine as a positive control and sterile Aquades as a negative control then incubated in an incubator at 37°C for 24 hours. The inhibition zone (clear area around the paper disc) was measured with a caliper (accuracy 0.02mm). The data obtained were tested for normality and homogeneity to determine whether or not there was a difference in the inhibitory power of banana mas (Musa acuminata lady finger) peel extract against Staphylococcus aureus bacteria. Results and Discussion: The results showed that at a concentration of 75% there was an inhibitory power for the growth of Staphylococcus aureus bacteria of 6.32 mm. Mas banana peel extract (Musa acuminata lady finger) has antibacterial content in the form of flavonoids, alkaloids, saponins and tannins which are able to inhibit the growth of Staphylococcus aureus bacteria in vitro. Conclusion: Mas banana peel extract (Musa acuminata lady finger) can inhibit the growth of Staphylococcus aureus bacteria in vitro with moderate criteria.